2022
DOI: 10.1021/acs.est.2c02780
|View full text |Cite
|
Sign up to set email alerts
|

Organotins Remain a Serious Threat to the Indo-Pacific Humpback Dolphins in the Pearl River Estuary

Abstract: Marine mammals often accumulate high levels of environmental contaminants, even those that are globally regulated regarding usage, raising concerns about their health status. Here, we conducted the first investigation of tissue distribution, spatiotemporal trends, and potential risks of six organotin compounds (OTs) in Indo-Pacific humpback dolphins (n = 101) from the northern South China Sea during 2003–2021. We detected the highest level of hepatic triphenyltin in these humpback dolphins compared with the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 68 publications
(152 reference statements)
0
4
0
Order By: Relevance
“…, Baikal seal and human beings) have revealed that co-exposure of PFAS with other hazardous contaminants ( e.g. , TBT, PBDE 47, TBBPA, and TCBPA) exhibits additional effects on PPAR at concentrations relevant for humpback dolphins. ,, Actually, the populations of PRE humpback dolphin accumulated mixtures of PFAS congeners and other environmental PPAR ligands, such as alternative halogenated flame retardants, organotins, and PCBs. ,, Thus, the potential health risks of high-level PFOS and other PFAS congeners in PRE dolphins are of concern.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…, Baikal seal and human beings) have revealed that co-exposure of PFAS with other hazardous contaminants ( e.g. , TBT, PBDE 47, TBBPA, and TCBPA) exhibits additional effects on PPAR at concentrations relevant for humpback dolphins. ,, Actually, the populations of PRE humpback dolphin accumulated mixtures of PFAS congeners and other environmental PPAR ligands, such as alternative halogenated flame retardants, organotins, and PCBs. ,, Thus, the potential health risks of high-level PFOS and other PFAS congeners in PRE dolphins are of concern.…”
Section: Resultsmentioning
confidence: 99%
“…pBIND-dolphin/human-PPARs all contain a yeast Gal4 DNA-binding domain, which can activate the GAL4-UAS-dependent LRG. The detailed procedures for LRG assay were carried out as previously described with some modifications. Briefly, HEK 293T cells were plated at a density of 4 × 10 4 cells per well in 96-well plates in phenol-red free Dulbecco’s modified Eagle’s medium supplemented with 10% fetal bovine serum. After cells attached to the wells overnight, the medium was replaced with opti-MEM I reduced serum medium (Invitrogen), and the cells were cotransfected with the fusion expression vector pBIND-dolphin/human-PPARs and the luciferase reporter vector pGL4.35­[luc2P/9XGAL4UAS/Hygro] at a mass ratio of 1:2 using the ViaFect Transfection Reagent (Promega).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tributyltin, a component of marine antifouling paint, can be enriched in the human body through the food chain, posing a threat to human health. , Tributyltin pollution is an important problem in some coastal areas. Butyltin in seafood from the Polish Baltic Sea coast is as high as 1132 ng Sn/g dw . In humans, median levels of total tin and organotin compounds detected in urine samples of pregnant women and adults in Iowa, USA, were 0.20 ng/mL and 0.57 ng/mL, respectively .…”
Section: Introductionmentioning
confidence: 99%